Vous êtes sur la page 1sur 15

# Chapter 2

2.1-1
Ae jφ  Ae jφ n = m
∫− T0 / 2
T0 / 2
j 2 π ( m−n )f 0t jφ
cn = e dt = Ae sinc( m − n ) = 
T0 0 otherwise

2.1-2

c0 v (t ) = 0
2 T0 / 4 2π nt T0 / 2 2π nt 2A πn
cn =
T0 ∫
0
A cos
T0
dt + ∫ ( − A)cos
T0 / 4 T0
dt =
πn
sin
2

n 0 1 2 3 4 5 6 7
cn 0 2A/π 0 2 A / 3π 0 2 A / 5π 0 2 A / 7π
arg cn 0 ±180° 0 ±180°

2.1-3

c0 = v (t ) = A / 2
2 T0 /2  2 At  2π nt A A
cn =
T0 ∫ 0
A−
 T0 
 cos
T0
dt =
πn
sin π n −
(π n) 2
(cos π n − 1)

n 0 1 2 3 4 5 6
cn 0.5A 0.2A 0 0.02A 0 0.01A 0
arg cn 0 0 0 0

2.1-4

2 T0 / 2 2π t
c0 =
T0 ∫
0
A cos
T0
=0 (cont.)

2-1
2 A  sin (π − π n ) 2t / T0 sin (π + π n ) 2t / T0 
T0 / 2
2 T0 / 2 2π t 2π nt
cn =
T0 ∫0
A cos
T0
cos
T0
dt = 
T0  4(π − π n) / T0
+
4(π + π n ) / T0  0

A/2 n = ±1
[ sinc(1 − n) + sinc(1 + n )] = 
A
=
2  0 otherwise

2.1-5

c0 = v (t ) = 0
2 T0 / 2 2π nt A
cn = − j
T0 ∫0
A sin
T0
dt = − j
πn
(1 − cos π n )

n 1 2 3 4 5
cn 2A/π 0 2 A / 3π 2 A / 5π
arg cn −90° −90° −90°

2.1-6

c0 = v(t ) = 0
2 A  sin (π − π n ) 2t / T0 sin ( π + π n ) 2t / T0 
T0 / 2
2 T0 / 2 2π t 2π nt
cn = − j
T0 ∫0
A sin
T0
sin
T0
dt = − j 
T0  4(π − π n ) / T0

4(π + π n )/ T0  0

m jA / 2 n = ±1
[sinc(1 − n ) − sinc(1 + n ) ] = 
A
= −j
2  0 otherwise

2.1-7
1  T0 / 2
v ( t) e− jnω0 t dt + ∫ v(t )e − jnω 0t dt ]
T0
cn = ∫
T0  0 T0 / 2

T0 T0 / 2
where ∫T0 / 2
v(t )e − jnω0 t dt = ∫
0
v (λ + T0 /2) e− jnω 0λ e− jnω 0T0 / 2 d λ
T0 / 2
= −e jnπ ∫ v (t )e − jnω0 t dt
0

## since e jnπ = 1 for even n, cn = 0 for even n

2-2
2.1-8

P = c0 + 2 ∑ cn = Af 0τ + 2 Af 0τ sinc f 0τ + 2 Af 0τ sinc2 f 0τ + 2 Af 0τ sinc3 f 0τ + L
2 2 2 2 2 2

n =1

1
where = 4 f0
τ
1 1 + 2sinc2 1 + 2sinc2 1 + 2sinc2 3  = 0.23 A2
A2
f > P= 
τ 16 4 2 4 
2 A2  1 1 3 5 3 7
f > P= 1 + 2sinc2 + 2sinc2 + 2sinc2 + 2sinc2 + 2sinc 2 + 2sinc 2  = 0.24 A2
τ 16  4 2 4 4 2 4
1 A 
2
1 1
f > P= 1 + 2sinc2 + 2sinc 2  = 0.21A2
2τ 16  4 2

2.1-9
 0 n even

cn =  2 2
 π n  n odd
 
2 2
1 T0 / 2  4t  2 T0 / 2  4t  1
a) P =
T0 ∫−T0 / 2  1 − T0  dt = T0 ∫
0
 1 −  dt =
 T0  3
2 2 2
 4   4   4 
P′ = 2  2  + 2  2  + 2  2 
= 0.332 so P′ / P = 99.6%
π   9π   25π 
8 8 8
b) v′(t ) = 2 cos ω 0t + 2 cos3ω 0t + cos5ω 0t
π 9π 25π 2

2.1-10
 0 n even

cn =  − j 2
 π n n odd

1  2 2  2  2  2 2 
∫−T0 / 2 (1) dt = 1 P = 2  π  +  3π  +  5π   = 0.933 so P′ / P = 93.3%
T0 / 2
a) P = ′
2

T0  

(cont.)

2-3
4 4 4
b) v′(t ) = cos ( ω0t − 90° ) + cos ( 3ω0t − 90° ) + cos ( 5ω 0t − 90°)
π 3π 5π
4 4 4
= sin (ω 0t ) + sin ( 3ω 0t ) + sin ( 5ω0t )
π 3π 5π

2.1-11
2
1 T0  t  1 1 / 2 n=0
P=
T0 ∫0
  dt =
 T0  3
cn = 
1 / 2π n n ≠ 0
∞ 4 4
 2  2  1 1 1  1
P =2∑   = 2    4 + 4 + 4 +L =
n odd  π n  π  1 3 5  3

1 1 1 4π 2 1 1  π2
Thus, + + + L = 3− 4= 6
12 22 32 2  

2.1-12
2
2 T0 / 2  4t  1 0 n even
P=
T0 ∫0
 1 −  dt =
 T0  3
cn = 
 (2/ π n) n odd
2

∞2 2
1  1  1 2 1 1 1  1
P =   + 2∑   = + 2  2 + 2 + 2 +L =
2 n =1  2π n  4 4π 1 2 3  3

1 1 1 π4 1 π 4
Thus, 4 + 4 + 4 + L = =
1 3 5 2 ⋅ 24 3 96

2.2-1
πt
τ /2
V ( f ) = 2∫ cos2π ftdt
A cos
0 τ
τ
 π
(
 sin τ −2π f 2 sin ) ( πτ 2π f ) τ2  Aτ
+
= 2A  + = [ sinc( f τ −1/2) + sinc( f τ + 1/2) ]
 2 π −2π f
τ ( 2 ) (πτ 2π f )  2
+
 
(cont.)

2-4
2.2-2
τ /2 2π t
V ( f ) = − j 2∫ A sin cos2π ftdt
0 τ

 sin τ (
2π −2π f τ sin
) ( 2τπ 2π f ) τ2  = − j Aτ sinc( f τ −1) − sinc( f τ + 1)
+
= − j2 A  2− [ ]

(
 2 τ −2π f )2 ( 2τπ 2π f )  2
+

2.2-3
τ t 2 Aτ   ωτ  
V ( f ) = 2∫  A − A  cos ω tdt =  2sin 2   − 1 + 1 = Aτ sinc f τ
2

 τ (ωτ )   2 
2
0

2.2-4
τ t 2 Aτ
V ( f ) = − j 2∫ A sin ω tdt = − j (sin ωτ − ωτ cos ωτ )
0 τ (ωτ ) 2
A
= −j (sinc2 f τ − cos2π f τ )
πf

2.2-5
1  f 
v (t ) = sinc2Wt ↔ Π 
2W  2W 
2
∞ ∞ 1  f  ∞ 1 1
∫ sinc2Wt dt = ∫ df = ∫
2
Π  df =
−∞ −∞ 2W  2W  −∞ 4W 2
2W

2-5
2.2-6
2πW
( Ae − bt ) dt =
A2 A2 A2

E=∫ E′ = 2∫ 2
2W
df = arctan
0 2b 0 b + (2π f )2
πb b
E′ 2 2πW 50% W = b / 2π
= arctan =
E π b 84% W = 2b / π

2.2-7
∞ ∞
 ∞ W ( f ) e jω t df dt
∫−∞
v ( t )w ( t ) dt = ∫−∞
v( t )
 ∫−∞ 
∞ ∞ ∞
= ∫ W ( f )  ∫ v (t) e− j (− ω ) t dt  df = ∫ W ( f )V (− f ) df
−∞  −∞  −∞
∞ ∞ ∞
∫ v 2 ( t ) dt =∫ V ( f )V * ( f )df = ∫ V ( f ) df
2
V ( − f ) = V * ( f ) when v (t) is real, so
−∞ −∞ −∞

2.2-8
∗ ∗

∫−∞ w∗ (t)e− j 2π ft dt =  ∫−∞ w(t )e j 2π ft dt  =  ∫−∞ w( t)e− j 2π ( − f )t dt  = W ∗ ( f )
∞ ∞ ∞

Let z ( t ) = w∗ ( t ) so Z ( f ) = W ∗ ( − f ) and W ∗ ( f ) = Z ( − f )
∞ ∞
Hence ∫−∞
v( t )z( t) dt = ∫ V ( f ) Z ( − f ) df
−∞

2.2-9
t  1  f 
Π   ↔ A sinc Af so sinc At ↔ Π  
 A A  A
2t τ  fτ  2
v (t ) = sinc ↔ V ( f ) = Π   for A =
τ 2  2  τ

2.2-10
πt  t  Bτ
B cos Π   ↔ [ sinc( f τ − 1/2) + sinc( f τ + 1/2) ]
τ τ  2
Bτ π (− f )  − f  πf  f 
so [sinc(tτ − 1/2) + sinc(tτ + 1/2) ] ↔ B cos Π  = B cos Π 
2 τ  τ  τ τ 
Let B = A and τ = 2W ⇒ z (t ) = AW [sinc(2Wt − 1/2) + sinc(2Wt + 1/2) ]

2.2-11
2π t  t  Bτ
B sin Π  ↔− j [sinc( f τ − 1) + sinc( f τ + 1) ]
τ τ  2
Bτ 2π (− f )  − f  2π f  f 
so − j [ sinc(tτ − 1) + sinc( tτ + 1) ] ↔ B sin Π  = − B sin Π 
2 τ  τ  τ τ 
Let B = − jA and τ = 2W ⇒ z ( t ) = AW [ sinc(2Wt − 1) + sinc(2Wt + 1) ]

2-6
2.2-12
2b 4π a a /π
e −b t ↔ ⇒ e−2π a t ↔ = 2
b + (2π f )
2 2
(2π a ) + (2π f )
2 2
a + f2

(e )
2
∞ 2 1 ∞ a /π a ∞ df
∫ =∫ ∫
−2 π a t
dt = df = 2  
2π a −∞ a + f π  (a + f2)
−∞ 2 2 0 2
2

2
∞ dx 1 π  1 π
Thus, ∫ =   = 3
(a + x2 ) 2  a  2π a 4 a
0 2
2

2.3-1
z (t ) = v (t − T ) + v( t + T ) where v( t ) = AΠ (t /τ ) ↔ Aτ sinc f τ
so Z( f ) = V ( f ) e− jω T + V ( f )e jωT = 2 Aτ sinc f τ cos2π fT

2.3-2
z (t ) = v (t − 2T ) + 2v( t ) + v( t + 2T ) where v(t ) = aΠ (t /τ ) ↔ Aτ sinc f τ
Z ( f ) = V ( f )e − j 2ωT + V ( f ) + V ( f )e j2ωT = 2 Aτ (sinc f τ )(1 + cos4π fT )

2.3-3
z (t ) = v (t − 2T ) − 2v( t ) + v( t + 2T ) where v (t ) = aΠ (t /τ ) ↔ Aτ sinc f τ
Z ( f ) = V ( f )e − j 2ωT − 2V ( f ) + V ( f )e j2ωT = 2 Aτ (sinc f τ )(cos4π fT − 1)

2.3-4
 t −T   t −T / 2 
v (t ) = AΠ   + ( B − A)Π  
 2T   T 
− j ωT
V ( f ) = 2 AT sinc2 fTe + ( B − A)T sinc fTe− jω T / 2

2-7
2.3-5
 t − 2T   t − 2T 
v (t ) = AΠ   + ( B − A)Π  
 4T   2T 
V ( f ) = 4 AT sinc4 fTe − j 2ωT + 2( B − A)T sinc2 fTe− j 2ωT

2.3-6
1
Let w(t ) = v( at ) ↔ W ( f ) = V ( f / a)
a
1
Then z (t ) = v[a(t − td / a)] = w(t − td / a) so Z ( f ) = W ( f ) e− jω td / a = V ( f / a) e− jω td / a
a

2.3-7
∞ ∞
F  v (t) e jω ct  = ∫ v(t )e jω ct e− jω t dt =∫ v (t) e− j 2π ( f − fc ) t dt =V ( f − f c )
−∞ −∞

2.3-8
v (t ) = AΠ (t /τ )cos ωc t with ω c = 2π f c = π / τ
Aτ Aτ Aτ
V( f ) = sinc( f − f c )τ + sinc( f + f c )τ = [ sinc( fτ − 1/2) + sinc( f τ + 1/2) ]
2 2 2

2.3-9
v( t ) = AΠ (t /τ )cos(ωc t − π /2) with ω c = 2π f c = 2π / τ
e− jπ / 2 e jπ / 2
V( f ) = Aτ sinc( f − f c )τ + Aτ sinc( f + f c )τ
2 2

= −j [sinc( f τ − 1) − sinc( f τ + 1) ]
2

2.3-10
2A
z (t ) = v (t) c o s ω ct v(t ) = Ae − t ↔
1 + (2π f ) 2
1 1 A A
Z ( f ) = V ( f − fc ) + V ( f + fc ) = +
2 2 1 + 4π ( f − f c ) 1 + 4π ( f + f c )2
2 2 2

2.3-11
A
z (t ) = v ()cos(
t ωc t − π /2) v (t ) = Ae −t for t ≥ 0 ↔
1 + j 2π f
e − jπ / 2 e jπ / 2 − jA / 2 jA / 2
Z( f ) = V ( f − fc) + V ( f + fc ) = +
2 2 1 + j 2π ( f − f c ) 1 + j 2π ( f + f c )
A/2 A/2
= −
j − 2π ( f − f c ) j − 2π ( f + f c )

2-8
2.3-12
 A t
v (t ) = t z (t ) z (t ) = Π
 ↔ 2 A sinc2 f τ
 τ  τ
d d  sin2π f τ  2A
Z ( f ) = 2A   =  (2πτ )2 f cos2π f τ − 2πτ sin2π f τ 
2 
df df  2π f τ  (2π f τ )
1 d − jA
V( f ) = Z( f ) = ( sinc2 f τ − cos2π f τ )
− j 2π df πf

2.3-13
−b t 2 Ab
z (t ) = tv (t ) v( t ) = Ae ↔
b + (2π f )
2 2

1 d  2 Ab  j 2 Abf
Z( f ) =  2 2
=
− j 2π df  b + (2π f )   b + (2π f ) 2 
2
2
 

2.3-14
A
z (t ) = t 2v( t ) v (t ) = Ae −t for t ≥ 0 ↔
b + j2π f
1 d  A  2A
Z( f ) =  b + j 2π f  =
( − j 2π f )  [ b + j 2π f ]
2 3
df 

2.3-15
1
v (t ) = e−π (bt) ↔ V ( f ) = e −π ( f / b)
2 2

b
d j 2π f −π ( f / b)2
( a) v (t ) = −2π b 2te −π ( bt ) ↔
2
e
dt b
1 d f −π ( f / b )2
(b ) te− π (bt) ↔ V( f ) =
2
e
− j 2π df jb
Both results are equivalent to bte −π ( bt ) ↔ − jf e−π ( f / b)
2 2

2.4-1
y (t ) = 0 t<0
2
t At
= ∫ Aλ d λ = 0<t <2
0 2
2
= ∫0 Aλ d λ = 2A t >2

2-9
2.4-2
y (t ) = 0 t < 0, t > 5
2
t At
= ∫ Aλ d λ = 0 <t< 2
0 2
= ∫0 Aλ d λ = 2 A
2
2<t <3
2 A
= ∫ Aλ d λ =  4 − ( t − 3) 2  3 < t < 5
t− 3 2

2.4-3
y (t ) = 0 t < 0, t > 3
t At 2
= ∫0 Aλ d λ = 0 < t <1
2
t A
= ∫ Aλ d λ = (2t − 1) 1< t < 2
t −1 2
2 A
= ∫ Aλ d λ =  4 − (t − 1) 2  2 < t < 3
t −1 2

2.4-4
y (t ) = 0 t <4
t
= ∫ 2 Ad λ = 2 At − 8 A 4 ≤ t ≤ 6
4
8
= ∫ 2A dλ = 4 A t >6
6

2-10
2.4-5
y (t ) = 0 t<0
t
= ∫ 2e−2λ d λ = 1 − e −2t 0 ≤t≤ 2
0
t
= ∫ 2e −2λ d λ = e −2t  e4 − 1 t>2
t− 2

2.4-6
y (t ) = 0 t < −1, t ≥ 3
t
= ∫ 2(1 + λ ) d λ = t2 + 2t + 1 −1 ≤ t < 0
−1
0 t
= ∫ 2(1 + λ ) d λ + ∫ 2(1 − λ )d λ = −t 2 + 2t + 1 0 ≤ t < 1
−1 0
0 1
= ∫ 2(1 + λ )d λ + ∫ 2(1 − λ ) d λ = −t 2 + 2t + 1 1 ≤ t < 2
t− 2 0
1
= ∫ 2(1 − λ ) d λ = t2 − 6t + 9 2≤t <3
t− 2

2.4-7
y (t ) = 0 t≤0
= ∫ Ae− aλ Be− b( t− λ )d λ =[ AB /( a − b)][ e− bt −e − at ] t > 0
t

2.4-8
j jπ t j − jπ t
v (t ) = Ae −at w(t ) = sin π t =
e − e = B1e −b1t + B2e− b2 t
2 2
y (t ) = v ∗ w1 (t ) + v ∗ w2 (t ) = [ AB1 /(a − b1 )][ e −b1t − e − at ] + [ AB2 /( a −b2 )][ e− b2 t − e − at ]
Let B1 = j /2, b1 = − jπ , B2 = − j /2, b2 = jπ and simplify

2.4-9

v ∗ w(t ) = ∫ v (λ )w(t − λ ) d λ let µ = t − λ
−∞
−∞ ∞
= − ∫ v (t − µ ) w( µ ) d µ = ∫ w( µ) v (t − µ )d µ = w ∗ v (t )
∞ −∞

2-11
2.4-10

Let y (t ) = ∫ v( λ ) w(t − λ )d λ where v( −t ) = v(t ), w(−t ) = w(t )
−∞
∞ ∞
y (−t ) = ∫ v (λ )w( −t − λ ) d λ = ∫ v (λ )w(t + λ ) d λ
−∞ −∞
∞ ∞
= − ∫ v( −µ ) w( t − µ ) d µ = ∫ v( µ ) w(t − µ )d µ = y (t )
−∞ −∞

2.4-11

Let y (t ) = ∫ v (λ )w(t − λ ) d λ where v ( −t ) = −v (t ), w(−t ) = −w(t)
−∞
∞ ∞
y (−t ) = ∫ v (λ )w(−t − λ ) d λ = − ∫ v (λ )w(t + λ ) d λ
−∞ −∞
∞ ∞
= ∫ v (− µ ) w(t − µ ) d µ = ∫ v (µ ) w( t − µ )d µ = y (t )
−∞ −∞

2.4-12
Let w(t ) = v ∗ v (t ) = τΛ (t /τ )
0 t +τ / 2
3
v ∗ w(t ) = ∫ (τ + λ) d λ + ∫
(τ − λ) d λ = τ 2 − t 2 0 ≤ t < τ / 2
t −τ / 2 0 4
2
τ 1 3 
= ∫t −τ / 2 (τ − λ) d λ =  t − τ  τ / 2 ≤ t < 3τ / 2
2 2 
 3 2 2
 4τ −t t <τ / 2

1 
2
3 
Thus v ∗ v ∗ v (t ) =   t − τ  τ / 2 ≤ t < 3τ / 2
2 2 
 0 t ≥ 3τ / 2

2.4-13
F {v (t ) ∗ [ w(t ) ∗ z (t )]} = V ( f ) [W (f )Z ( f )] = [V ( f )W( f ) ] Z ( f )
so v (t ) ∗[w(t ) ∗ z (t) ] = F −1 {[V ( f )W( f )]Z ( f )} = [v( t ) ∗ w(t) ] ∗ z (t )

2-12
2.4-14
1 f 
V( f ) = Π   W ( f ) = 4Π (2 f )
4 4
Y ( f ) = V ( f )W( f ) = Π (2 f ) ↔ y (t ) = (1/2)sinc( t /2)

2.5-1
t Aτ Aτ
z (t ) = AΠ   cos ωc t Z ( f ) = sinc( f − f c )τ + sinc( f + f c )τ
τ  2 2
As τ → 0 the cosine pulse z (t) gets narrower and narrower while maintaining height A.
This is not the same as an impulse since the area under the curve is also getting smaller.
As τ → 0 the main lobe and side lobes of the spectrum Z ( f ) get wider and wider, however
the height gets smaller and smaller. Eventually the spectrum will cover all frequenci es with
almost zero energy at each frequency. Again this is different from what happens in the case
of an impulse.

2.5-2
 
W ( f ) = v ( f )e − j 2π ftd =  ∑ cv ( nf 0 )δ ( f − nf 0 )  e− j 2π ftd
 n 
= ∑ cv ( nf 0 ) e − j 2π n f0 t d
δ ( f − nf 0 ) ⇒ cw ( nf 0 ) = cv (nf 0 )e − j2π n f0 td
n

2.5-3
 
W ( f ) = j 2π fV ( f ) = j 2π f  ∑ cv (nf 0 )δ ( f − nf 0 )  = ∑ [ j 2π nf 0 cv ( nf 0 ) ]δ ( f − nf 0 )
 n  n
⇒ cw ( nf 0 ) = j 2π nf 0 cv ( nf 0 )

2.5-4
1 1 
W( f ) = [V ( f − mf0 ) ] = ∑ cv ( nf0 )δ ( f − kf0 − mf0 ) + ∑ cv ( nf0 )δ ( f − kf0 + mf0 ) 
2 2 n n 
1 
= ∑ cv [(k − m) f 0 ]δ ( f − kf 0 ) + ∑ cv [(k + m) f 0 ]δ ( f − kf 0 ) 
2 k k 
1
= ∑ {cv [(n − m) f 0 ] + cv [(n + m) f 0 ]}δ ( f − nf 0 )
n 2

1
so cw ( nf 0 ) = {cv [(n − m) f 0 ] + cv [(n + m) f 0 ]}
2

2-13
2.5-5
v (t ) = Au (t ) − Au (t − 2τ )
 1 1  1 1  − j 4π f τ 
V( f ) = A + δ ( f ) − + δ ( f ) e 
 j 2π f 2  j 2π f 2  
− j 4π ft − j0
But δ ( f ) e = e δ ( f ), so

V( f ) =
A
j 2π f
(1 − e − j 4π fτ ) = 2 Aτ sinc2 f τ e − j 2π f τ

 t −τ  − j 2π f τ
Agrees with v( t ) = Π   ↔ 2 Aτ sinc2 f τ e
 2τ 

2.5-6
v (t ) = A − Au (t + τ ) + Au (t − τ )
  1 1   1 1  
V ( f ) = A δ ( f ) −  + δ ( f )  e j 2π f τ −  + δ ( f )  e− j 2π fτ 
  j 2π f 2   j 2π f 2  
j 2π f τ − j 2π f τ
But δ ( f ) e = δ ( f )e = e δ ( f ), so
j0

 
V ( f ) = A δ ( f ) −
1
j 2π f
( e j 2π f τ − e− j2π f τ )  = Aδ ( f ) − 2 Aτ sinc2 f τ
 
Agrees with v( t ) = A − AΠ (t / 2τ ) ↔ Aδ ( f ) − 2 Aτ sinc2 f τ

2.5-7
v (t ) = A − Au (t + T ) − Au( t − T )
  1 1  j 2π fT  1 1  − j 2π fT 
V ( f ) = A δ ( f ) −  + δ ( f ) e − + δ ( f ) e 
  j 2π f 2   j 2π f 2  
But δ ( f ) e j 2π fT = δ ( f ) e− j2π fT = e j 0δ ( f ) = δ ( f ), so
−A −A
V( f ) =
j 2π f
( e j 2π fT + e − j2π fT ) =
jπ f
cos2π fT

−A
If T → 0, v(t ) = − A sgn t ↔ V ( f ) = , which agrees with Eq. (17)
jπ f

2.5-8
V ( f ) = sinc f ε and V (0) = 1, so
sinc f ε 1
W(f ) = + δ(f)
j 2π f 2
1 1
If ε → 0, w( t ) = u (t ) and W ( f ) = + δ ( f ), which agrees with Eq. (18)
j 2π f 2

2-14
2.5-9
1/ ε
V( f ) = and V (0) = 1, so
1/ ε + j 2π f
1/ ε 1
W(f ) = + δ(f )
( j 2π f )(1/ ε + j 2π f ) 2
1 1
If ε → 0, w( t ) = u (t ) and W ( f ) = + δ ( f ), which agrees with Eq. (18)
j 2π f 2

2.5-10
z (t ) = AΠ ( t / τ ) ∗ [δ (t − T ) +δ (t + T ) ]
so Z( f ) = ( Aτ sinc f τ ) ( e− jω T + e jωT ) = 2 Aτ sinc f τ cos2π fT

2.5-11
z (t ) = AΠ ( t / τ ) ∗ [δ (t − 2T ) + 2δ (t ) + δ (t + 2T ) ]
so Z ( f ) = ( Aτ sinc f τ ) ( e − jω 2T + 2 + e jω 2 T ) = 2 Aτ sinc f τ (1 + cos4π fT )

2.5-12
z (t ) = AΠ ( t / τ ) ∗ [δ (t − 2T ) − 2 δ ( t ) + δ (t + 2T ) ]
so Z ( f ) = ( Aτ sinc f τ ) ( e − jω 2T − 2 + e jω 2T ) = 2 Aτ sinc fτ (cos4π fT − 1)

2.5-13

n 0 1 2 3 4 5 6 7 8
sin(π t) δ (t − 0.5n) 0 1 0 1 0 1 0 1 0
v (t ) 0 1 1 2 2 3 3 4 4

2.5-14
n -10 -9 -8 -7 -6 -5 -4 -3 -2 -1 0
cos(2π t )δ (t − 0.1n) 1 0.81 0.31 -0.31 -0.81 -1 -0.81 -0.31 0.31 0.81 1
v (t ) 1 1.81 2.12 1.81 1 0 -0.81 -1.12 -0.81 0 1

2-15